PENGARUH MOTIVASI KERJA DAN KEMAMPUAN MENGAJAR GURUTERHADAP PRESTASI BELAJAR SISWA PADA GUGUS IISEKOLAH DASAR KECAMATAN KEBAYAKAN KABUPATEN ACEH TENGAH - Fatmasari Fatmasari (Universitas Islam Negeri Ar-Raniry, 2014)
Motivation is one of the superior tools in order subordinate willing to work hard and smart in accord with the goal. If there is one achieve his or her motivation, then he or she tend to be continuously motivated. On the other hand, if there is one often fail to reach his or her motivation, then he or she keep preserving and keep make effort and pray till his or her motivation be reached or becomes hopeless. This study is aimed at knowing if there is a significant relationship between work motivation and teacher teaching ability toward the students’ achievement in Gugus II Primary School, Kebayakan Sub-district, Aceh Tengah. This study uses a quantitative approach with descriptive methods. The populations of the study were all the teachers and students at Gugus II Primary School Kebayakan sub-district, Aceh Tengah. The samples of the study were 31 teachers and 31 students. The results of this study indicate that the first hypothesis that there is a positive effect on work motivation with student achievement (rx1y = 0.670), second, there is a positive effect of the teachers teaching ability on the student achievement (rx2y = 0.691), there are three positive influence on work motivation and teachers teaching ability upon the achievement (rx1x2 = 0.856). The simultaneous analysis indicates that work motivation and the teachers teaching ability could affect the students’ achievement. Out of motivation variable hypothesis on the teacher high teaching ability has a significant influence on students’ achievement in Gugus II Primary School, Kebayakan sub-district, Aceh Tengah